Effects of customer retention strategies on customer retention – a case study of the banking industry in Kenya - Kaguri, Magdalene Njoki (Strathmore University, 2016)
The purpose of the study was to examine the perception of customer relationship managers on effects of customer retention strategies on customer retention in Kenya’s banking industry. The study examined how three customer retention strategies: customer relationship management, relationship marketing and perceived pricing tactics affect customer retention in the Kenyan banking sector. The respondents of the study were customer relationship managers of all the 43 banks surveyed. Using a questionnaire, data were collected from the banks. Correlation analysis was used. Customer Relationship Management (CRM) had a moderately strong positive relationship with customer retention. Price Perceived tactic was used to establish the extent to which customer relationship managers perceived that the pricing of their products and services to affect customer retention. There was a weak positive relationship between price tactic and customer retention. This weak relationship was attributed to the fact that most prices are regulated in the industry and as a result, it may not be a very good indicator of customer retention strategies. Customers may fail to switch service providers owing to the standardizing of products, services and prices. On relationship marketing there was a very weak positive relationship with customer retention, contrary to previous studies. This was attributed to product customization was not common in the market, and the ‘know your customer’ procedures appeared to be similar in different banks. As such, customers may fail to switch services providers because the relationship marketing appears similar across banks. Again, this appeared not to be a strong indicator of customer retention. The study therefore concludes that in sectors with similar products and prices, customer retention will largely be driven by customer relationship management. The study recommends that banks invest more in managing relationships with their customers as a way of retaining them, and attracting new customers. Customer relationship management will give them more competitive advantage than pricing or relationship marketing.
Submitted in Partial fulfilment of requirement for the degree of Master of Commerce at Strathmore University.
Keywords: Customer retention strategies; Customer retention; Banking industry; Kenya